2012
DOI: 10.1016/j.jhazmat.2012.01.062
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the wash-off of traffic related semi- and non-volatile organic compounds from urban roads under climate change influenced rainfall characteristics

Abstract: Traffic generated semi and non volatile organic compounds (SVOCs and NVOCs) pose a serious threat to human and ecosystem health when washed off into receiving water bodies by stormwater. Climate change influenced rainfall characteristics makes the estimation of these pollutants in stormwater quite complex. The research study discussed in the paper developed a prediction framework for such pollutants under the dynamic influence of climate change on rainfall characteristics. It was established through principal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Research is being conducted in the water environment in various countries: the Netherlands (surface water and river) [22], Greece (surface water) [23], Portugal (surface water) [24], Belgium (surface water) [25], Japan (rainwater) [26,27], the USA (rainwater) [28], Austria (rainwater) [29], Serbia (rainwater) [30], Nigeria (surface water, effluent of M/IWTP) [18], Taiwan (effluent of M/IWTP, rainwater, surface water) [31,32], China (effluent of M/IWTP) [6], and South Korea (surface water, effluent of M/IWTP) [5]. The reported concentration range of VOCs in the water environment ranged from several ng/L to mg/L, and was mainly the highest in the effluent of IWTP.…”
Section: Literature Review Of Vocs In Watermentioning
confidence: 99%
See 2 more Smart Citations
“…Research is being conducted in the water environment in various countries: the Netherlands (surface water and river) [22], Greece (surface water) [23], Portugal (surface water) [24], Belgium (surface water) [25], Japan (rainwater) [26,27], the USA (rainwater) [28], Austria (rainwater) [29], Serbia (rainwater) [30], Nigeria (surface water, effluent of M/IWTP) [18], Taiwan (effluent of M/IWTP, rainwater, surface water) [31,32], China (effluent of M/IWTP) [6], and South Korea (surface water, effluent of M/IWTP) [5]. The reported concentration range of VOCs in the water environment ranged from several ng/L to mg/L, and was mainly the highest in the effluent of IWTP.…”
Section: Literature Review Of Vocs In Watermentioning
confidence: 99%
“…The most important aspects of monitoring research are that well-managed analytical equipment, and various application methods for gas and liquid chromatography (GC and LC) are used. The method detection limit (MDL) and limit of quantitation (LOQ) differ for each compound, but are mainly between several ng/L and tens of ng/L [5,6,18,[22][23][24][25][26][27][28][29][30][31][32]. The most important method for water environment management is obtaining accurate monitoring and analysis results, and the accumulated results will be used as important data for policy decisions.…”
Section: Literature Review Of Vocs In Watermentioning
confidence: 99%
See 1 more Smart Citation
“…() showed significant traffic and climate change impacts on water quality by measuring build‐up and wash‐off of heavy metals and petroleum hydrocarbons. Mahbub et al ., () also predicted wash‐off of traffic‐related semi‐ and non‐volatile organic compounds from urban roads under climate change‐influenced rainfall characteristics. Ha and Stenstrom () developed a predictive model for stormwater runoff on a GIS platform based on the unit area loading method and Browne's empirical relation for soil characteristics.…”
Section: Introductionmentioning
confidence: 92%
“…Bäckström et al (2003) reported a winter driven climatic pattern for speciation and transport of heavy metals in road runoff and roadside total deposition at two Swedish sites. Field-experimental simulations with anticipated rainfall regimes (associated with projected climate change) in the Australian Gold Coast region showed dominating controls of moderate to high rainfalls, low to moderate rainfalls, and low to high rainfalls on the wash-off of, respectively, heavy metals (Mahbub et al, 2010), semi-and non-volatile organic compounds (Mahbub et al, 2012), and volatile organic compounds (Mahbub et al, 2011) from urban roads.…”
Section: Introductionmentioning
confidence: 99%